GREEN SYTHESIS OF CUO USING Citrus x microcarpa BUNGE PEEL EXTRACT AND ANTIBACTERIAL ACTIVITY EVALUATION - Afriani, Fitri; Lingga, Rahmad; Rafsanjani, Rifqi Almusawi; Tiandho, Yuant (Science Technology and Management Journal, 2025)
This article aims to synthesize CuO nanoparticles using the green synthesis method using Citrus x microcarpa Bunge peel extract, analyze their characteristics, and evaluate their antibacterial activity against the S. aureus. We investigated the role of the accelerator agent NaOH in the green synthesis of CuO nanoparticles. The presence of green synthesized CuO nanoparticles was confirmed by UV-Vis spectrophotometer and XRD. The use of NaOH in the green synthesis of nanoparticles accelerates the emergence of absorbance peaks around 400 nm, related to CuO's surface plasmon frequency. Calculation of crystallite size based on XRD diffractogram shows that NaOH can also act as a reducing agent. The smaller size of CuO nanoparticles will increase their stability when heated. In addition, green synthesized CuO nanoparticles showed high antimicrobial activity against S. aureus pathogens. These results indicate that CuO nanoparticles with antibacterial activity can be synthesized using an environmentally friendly and simple method.